Results of Malnutrition Correction in Children with Cystic Fibrosis with Hypercaloric Formulas for Enteral Nutrition for One Month: Cohort Study - Tatiana Y. Maksimycheva; Elena I. Kondratyeva; Victoria D. Sherman; Anna Y. Voronkova; Anna Y. Kulevatova ("Paediatrician" Publishers LLC, 2021)
Background. The use of hypercaloric formulas in cystic fibrosis patients has the risks of negative effects on carbohydrate and lipid metabolism. Thus, it is interesting to analyze the efficacy of malnutrition correction and the safety of hypercaloric enteral products with a low glycemic index and with medium-chain triglycerides content of 50%.Objective. The aim of the study is analyze the efficacy of malnutrition correction with therapeutic hypercaloric product for enteral nutrition in children with cystic fibrosis.Methods. The study included patients aged from 3 to 18 years with malnutrition (BMI < 50 percentile) who were prescribed therapeutic hypercaloric formula to correct the malnutrition. Anthropometric indicators (height, body weight), actual nutritional status, pancreatin doses, lung function, carbohydrate metabolism rates, and cholestasis marker (bile acid concentration) were measured initially and after 1 month of using formula nutrition.Results. The children' body weight (Me) has increased from 24.5 (21.2; 38.7) to 25.3 kg (21.6; 39.7) (p = 0.001), growth (Me) - from 133.5 (120.2; 146.5) to 136.5 cm (123.0; 148.5) (p < 0.001) after 1 month of using hypercaloric formula. The growth percentile increased from 33 to 40, the z-criterion values - from -0.5 to -0.3 SD (p < 0.001). There was no increase in BMI in dynamics due to the fact that the growth of children was ahead of body weight increase. The daily energy intake increased by an average of 450 kcal that was 21.8% regarding physiological need.Conclusion. The inclusion of hypercaloric formula in the diet of children with cystic fibrosis for 1 month significantly increases the indicators of linear growth and positively affects the overall physical development. There were no negative effect of formula on carbohydrate and lipid metabolism.